The effects of indomethacin, furosemide and prostaglandin F2 alpha on thyroid hormone levels in rams - Karahan, I; Pirinçci, I; Atessahin, A; Gürsu, F; Çikim, G; Güler, O (Tubitak Scientific & Technological Research Council Turkey, 2002)
This study was carried out to investigate the changes occurring in the levels of serum thyroid hormone in rams given indomethacin, furosemide and PGF2alpha. In the study. 20 Akkaraman rams, approximately 2 years old were used. Indomethacin (3.0 mg/kg), furosemide (2.0 mg/kg) and PGF2alpha (0.1 mg/kg) were intramuscularly given to the animals in one dose and repeated for four consecutive days. Blood samples were collected after drug administrations. Free-total thyriiodothyrionine and thyroxine (T3 and T4) levels were determined using a hormone autoanalyser. Serum free T3 and T4 levels in rams given PGF2alpha were found to have fallen compared to the control group and found to have increased in rams given indomethacin. On the other hand, it was established that serum total T3 and T4 levels increased in the rams given furosemide or PGF2alpha, but total T3 and T4 levels did not change in the animals given indomethacin. In conclusion, indomethacin, furosemide and PGF2alpha were found to have an effect on the levels of serum thyroid hormones in the rams.
Koçlarda i?ndometasin, furosemid ve prostaglandin F2 alfa'nin tiroid hormon düzeyleri üzerine etkileri
Keywords: prostaglandin F2 alpha; furosemide; indomethacin; thyroid hormones